Teaching Amidst the Pandemic: Exploring the Perceptions and Experiences of Teachers in Remote Rural Municipalities in the Philippines - Legarde, Michael Angelo A.; Sumandal, Arman H. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The world has been shaken by the advent of the COVID-19 pandemic, which has resulted in a dramatic loss of human life and poses an unprecedented challenge to almost all aspects of life, and the Philippines has not been an exception to these challenges. As a result, this deadly situation has flipped the offline teaching process and paved the way towards online-based teaching. This study was conducted to determine the perceptions and experiences of teachers in the remote areas towards online teaching. This study employed a cross-sectional explanatory research design and the analyses reveal that respondents with "high" technological proficiency are more likely to have a "positive" attitude toward online education whereas respondents with "poor" technological skills are more likely to have a "negative" attitude toward online learning. This strongly suggest that educational leaders may venture on training teachers on how to develop their technological knowledge and skills since it has a significant impact to their attitude towards online teaching. Moreover, further analysis also reveals that the relationship between teacher-respondents’ perceptions towards online teaching and their technological knowledge and skills was statistically significant. It is also recommended that training in online teaching needs to be provided to teachers to widen their understanding of online teaching.